Self-determination, motivation and study engagement: an empirical study - Hassan, Arif; Al Jubari, Ibrahim Hizam Ali (2013)
The paper examines the role of learning climate (autonomy supportive vs. controlling), intrinsic motivation resulting from the three basic needs satisfaction, as posited by Self Determination Theory of motivation, self-perception of choice and self-awareness on students’ study engagement. The data were collected from 529 undergraduates students (Females = 57.7% and 81.7% Malaysians) representing several study disciplines. Standardized instruments were employed to measure the constructs of learning climate, basic needs, perceived self-determination, and study engagement. Results provided strong support to the SDT proposition suggesting that an autonomy supportive learning climate significantly contributed to intrinsic need satisfaction of autonomy, competence, and relatedness. It was also found that the autonomy supportive learning climate and satisfaction of competency need contributed to study engagement. The study provides good empirical support to the SDT propositions from a non-Western cultural context.